Understanding the elastic bending mechanism in a 9, 10-anthraquinone crystal through thermal expansion study. Issue 34 (2nd June 2021) - Rather, Sumair A.; Saha, Binoy K.
Abstract : Thermal expansion study has been used to understand the mechanism of elastic bending in 9, 10-anthraquinone. Expansion along the bending axis due to bending is expected to resemble the thermal expansion along the same direction. Abstract : The crystal structures of Cu(acac)2 and 9, 10-anthraquinone are very similar and both of them exhibit elastic bending. The mechanism of thermal expansion has been correlated with the mechanism of bending for Cu(acac)2 . Then this idea has been used to postulate the bending mechanism in a 9, 10-anthraquinone crystal from a thermal expansion study.